Estimation of SIR model’s parameters of COVID-19 in Algeria - Mohamed Lounis; Dilip Kumar Bagal (Bulletin of the National Research Centre, 2020)
Abstract Background The coronavirus disease 2019 (COVID-19) is reported in Algeria on February 25th, 2020. Since then, the number is still increasing leading to a total number of 36,699 cases and 1333 deaths on August 12th, 2020. Thus, comprehension of the epidemic curve is very important to predict its evolution and subsequently adapt the best prevention strategies. In this way, the current study was conducted to estimate the parameters of the classical SIR model and to predict the peak of the COVID-19 epidemic in Algeria using data from February 25th, 2020 to August 12th, 2020. Results Results showed that the peak of the epidemic will be reached on September 8th, 2021 and the total infected persons will exceed 800,000 cases at the end of the epidemic. Also, more than 15 million persons will be susceptible. The reproduction number (R 0) is estimated at 1.23254. Conclusion These results may be helpful for the Algerian authorities to adapt their strategies and may be taken into consideration in the future phase of discontainment.